2011
DOI: 10.5336/medsci.2009-14563
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevalence and Its Association with Metabolic Risk Factors: Tokat Province Prevalence Study

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Obe zi te, cid di sos yal ve psi ko lo jik et ki le riy le tüm yaş ve sos yo-eko no mik grup la rı il gi len di ren komp leks bir has ta lık tır. Gün cel ça lış ma lar, Türk top lu mun da obe zi te pre ve lan sı nın art mak ta ol du ğu nu gös -ter mek te dir. Ça lış ma mız da, To kat ili kent sel ve kır sal alan la rın da obe zi te pre va lan sı nı ve me ta bo lik risk faktör le riy le iliş ki si ni be lir le mek amaç lan mış tır. G Ge e r re eç ç v ve e Y Yö ön n t te em m l le er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…27 In research conducted in Tokat, the average values of BMI were found to be 25.7 in men and 27.9 kg/m 2 in women; the prevalence of obesity was found to be 33.6 in women and 12.9 in men, and, in women, meaningful level of high obesity frequency was observed. 28 In this research, according to the BMI values of women, it was determined that a statistically significant difference was not present between age, PrBG, and PoBG a statistically significant difference was determined, however, between the average values of WC (P<0.000), total cholesterol level (P<0.050), HDL-c (P<0.026), LDL-c (P<0.006), and triglyceride (P<0.024). According to the BMI values of men, it was determined that there was no statistically total cholesterol significant difference between age, PrBG, total cholesterol, HDL-c, and LDL-c.…”
Section: Discussionmentioning
confidence: 81%
“…27 In research conducted in Tokat, the average values of BMI were found to be 25.7 in men and 27.9 kg/m 2 in women; the prevalence of obesity was found to be 33.6 in women and 12.9 in men, and, in women, meaningful level of high obesity frequency was observed. 28 In this research, according to the BMI values of women, it was determined that a statistically significant difference was not present between age, PrBG, and PoBG a statistically significant difference was determined, however, between the average values of WC (P<0.000), total cholesterol level (P<0.050), HDL-c (P<0.026), LDL-c (P<0.006), and triglyceride (P<0.024). According to the BMI values of men, it was determined that there was no statistically total cholesterol significant difference between age, PrBG, total cholesterol, HDL-c, and LDL-c.…”
Section: Discussionmentioning
confidence: 81%
“…A 2010 study and subsequent studies have found obesity to be between 23% and %43. These studies also found that obesity varies from region to region (9)(10)(11). Similarly, data also show the prevalence of obesity in primary school age and adolescents in Türkiye to be high.…”
Section: Introductionmentioning
confidence: 90%
“…It is thought that the duration of obesity and its type, that is, central type fat accumulation, is more effective in the development of diabetes mellitus and glucose intolerance than the degree of obesity [15,16]. A study conducted by Kutlutürk et al [17] investigated the relationship between obesity and metabolic risk factors and found a significant relationship between obesity and fasting serum glucose levels. Innocent et al…”
Section: ! "#$%And!h(!)*+#-/*0!*1!/and-;+!e5#+0!8'i!%andeand%/!0!2-*;/! <#-#$%And/! =-*;!:! >0!?!@@mentioning
confidence: 99%